Blood clot formation does not affect metastasis formation or tumor growth in a murine model of breast cancer. - Stephanie Rossnagl; Anja von Au; Matthaeus Vasel; Marco G Cecchini; Inaam A Nakchbandi (PLoS ONE, 2014)
Cancer is associated with increased fracture risk, due either to metastasis or associated osteoporosis. After a fracture, blood clots form. Because proteins of the coagulation cascade and activated platelets promote cancer development, a fracture in patients with cancer often raises the question whether it is a pathologic fracture or whether the fracture itself might promote the formation of metastatic lesions. We therefore examined whether blood clot formation results in increased metastasis in a murine model of experimental breast cancer metastasis. For this purpose, a clot was surgically induced in the bone marrow of the left tibia of immundeficient mice. Either one minute prior to or five minutes after clot induction, human cancer cells were introduced in the circulation by intracardiac injection. The number of cancer cells that homed to the intervention site was determined by quantitative real-time PCR and flow cytometry. Metastasis formation and longitudinal growth were evaluated by bioluminescence imaging. The number of cancer cells that homed to the intervention site after 24 hours was similar to the number of cells in the opposite tibia that did not undergo clot induction. This effect was confirmed using two more cancer cell lines. Furthermore, no difference in the number of macroscopic lesions or their growth could be detected. In the control group 72% developed a lesion in the left tibia. In the experimental groups with clot formation 79% and 65% developed lesions in the left tibia (p = ns when comparing each experimental group with the controls). Survival was similar too. In summary, the growth factors accumulating in a clot/hematoma are neither enough to promote cancer cell homing nor support growth in an experimental model of breast cancer bone metastasis. This suggests that blood clot formation, as occurs in traumatic fractures, surgical interventions, and bruises, does not increase the risk of metastasis formation.